Epidemic Threats to the European Union: Expert Views on Six Virus Groups. Issue 4 (4th July 2012) - Kelly, L.; Brouwer, A.; Wilson, A.; Gale, P.; Snary, E.; Ross, David; de Vos, C. J.
Summary In recent years, several animal disease epidemics have occurred within the European Union (EU). At the 4th Annual Meeting of the EPIZONE network (7–10 June 2010, St. Malo, France), an interactive session was run to elicit the opinions of delegates on a pre‐defined list of epidemic threats to the EU. Responses from over 190 delegates, to questions relating to impact and likelihood, were used to rank six virus groups with respect to their perceived threat now (2010) and in 2020. The combined opinions of all delegates suggested that, from the pre‐selected list of virus groups, foot‐and‐mouth disease and influenza are currently of most concern. Delegates thought that influenza would be less of a threat and zoonotic arboviruses would be more of a threat in 2020. Although the virus group rankings should not be taken as definitive, the results could be used in conjunction with experimental and field data, by scientists, policy‐makers and stakeholders when assessing and managing risks associated with these virus groups.